Classifying non-functional properties of software systems according to their use in some application areas - Md Sultan, Abu Bakar; Bello, AbdulKarim; Zulzalil, Hazura; Abd Ghani, Abdul Azim (Medwell Journals, 2018)
Dealing with non-functional properties has a great challenge to software engineers for many years. For many years, software engineers are using this properties provide high quality to the software products they developed. This make it possible for engineers to divide their focus of testing non-functional properties according to, the services the software product renders. Although, non-functional properties of software systems are being described as the most important contributors to the success of software systems, study to date revealed that there is no general consensus on the notion of certain classification of NFPs. This study presents results of a study on the investigation conducted on the different classification of Non-Functional Properties (NFP) of software systems.